Especies arbóreas más comunes de las zonas ganaderas de la Provincia de Tucumán que sirven de alimento al ganado - DIAZ, H. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The author discusses the importance of arboreal vegetation as a source of forage in the various cattle producing zones of the province of Tucumán, in northern Argentina and gives the results of observations concerning the palatability of 20 species. The moisture content of the fresh material the composition of the leaves and twigs and the mature fruits on a dry matter basis, the total digestible nutrients and the nutritive ratios are tabulated.